'An eye more penetrating than other men's': Finding the Recherche's Narrator in a World of Experts. Issue 1 (March 2022) - Beitler, Ben
Abstract : This essay presents the Recherche 's narrator as an expert in a world of experts. Considering previous scholarship on the sociological knowledge present in Proust's novel, I imagine the pursuit of this knowledge as characterizing its narrator, distinguishing him from the other specialists who populate the pages of his récit. Drawing on the work of Gil Eyal, I read this récit as displaying a marked attention to the 'networks of expertise' in which these other experts make their knowledge effective. The récit 's language, meanwhile, provides information on the network of expertise in which the narrator himself must operate to assume the social position of expert. Ultimately, I argue that thinking about the narrator and his writing in terms of expertise allows us to ironize the narrator's knowledge about the social world. From this ironic distance, the Recherche becomes not a vehicle of such knowledge but an experience of it.